DETERMINANTS OF BANKING CAPITAL BUFFER IN INDONESIA - Nurhikmah Fauziah; Farah Wulandari (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2020)
Banks as intermediary institutions that play an important role in the economy are required to be in a healthy state since the bank conditions reflect macroeconomic conditions. To achieve the goal of financial system stability, the banking regulator issued Basel regulations. The regulation contains provisions for banks to provide a capital buffer as an effort to strengthen bank capital from risks that may arise. The purpose of this research is to find out what factors affect the bank's capital buffer with the object of research on conventional commercial banks in Indonesia from 2010 to 2019. The method used in this research is panel data regression with independent variables, i.e. GDPG, SIZE, ROE, LOTA, NPL, BIRATE, LDR, and BOPO, as well as the dependent variable capital buffer. The results showed that all the dependent variables used had a significant effect both simultaneously and partially on the capital buffer.